Water Quality : An Introduction - Boyd, Claude E. (USA Springer, 2015)
This book presents the basic aspects of water quality, emphasizing physical, chemical, and biological factors. The study of water quality draws information from a variety of disciplines including chemistry, biology, mathematics, physics, engineering, and resource management. University training in water quality is often limited to specialized courses in engineering, ecology, and fisheries curricula. This book also offers a basic understanding of water quality to professionals who are not formally trained in the subject. The revised second edition updates and expands the discussion, and incorporates additional figures and illustrative problems. Improvements include a new chapter on basic chemistry, a more comprehensive chapter on hydrology, and an updated chapter on regulations and standards. Because it employs only first-year college-level chemistry and very basic physics, the book is well-suited as the foundation for a general introductory course in water quality. It is equally useful as a guide for self-study and an in-depth resource for general readers.
Keywords: Marine sciences; Freshwater; Agriculture; Aquatic ecology .; Geochemistry; Marine & Freshwater Sciences; Agriculture; Freshwater & Marine Ecology; Geochemistry